Shifting Landscapes: Remapping The Writing Traditions of Islamic Southeast Asia through Digitisation - Annabel Teh Gallop (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2020)
Studies of the languages and literatures of the Malay world of Nusantara have long been shaped by the collections of manuscripts held in western institutions, which strongly reflect the interests of colonial officials who formed them. A very different picture of the writing traditions of maritime Southeast Asia emerges from a survey of manuscripts still held in local communities digitised through the Endangered Archives Programme and DREAMSEA. Primarily concerned with Islamic topics and often written in Arabic, the study of these newly-accessible collections has the potential to lead to a remapping of the intellectual landscape of the region.